OPTIMALISASI KEGIATAN BHABINKAMTIBMAS DALAM PENYELESAIAN PERKARA RINGAN DI WILAYAH HUKUM POLSEK CIANJUR KOTA - HAFIM, HAFIM RASYDIN (Advances in Police Science Research Journal, 2019)
The light case that occurred among the people of Cianjur City Subdistrict has now been settled amicably through a problem solving method. But in its implementation problem solving is still not optimally done. In this thesis, there are three issues discussed, namely the implementation of Bhabinkamtibmas activities at this time, the factors that influence the implementation of Bhabinkamtibmas activities, the methods used in the implementation of Bhabinkamtibmas activities. The purpose of this research is to describe the implementation of Bhabinkamtibmas activities, describe the factors that influence them and describe the methods used in carrying out light case Bhabinkamtibmas activities. This research uses a qualitative approach and is carried out in the Cianjur Sub-district of the city, Cianjur Regency. The research findings show that the activities of Bhabinkamtibmas in the settlement of minor cases in the Cianjur city police station have been running, but in their implementation there are still some shortcomings that are not optimal. In addition there are factors that hinder and support these activities so that the settlement of minor cases can be carried out properly. And in the implementation of the light case settlement by Bhabinkamtibmas using the mediation method, it was considered appropriate for the character of the Cianjur City Subdistrict community. In the implementation of Bhabinkamtibmas activities analyzed with motivation theory, inhibiting or supporting factors from the implementation of Bhabinkamtibmas activities were analyzed with theories of factors affecting law enforcement, while in the mediation methods used in the settlement of minor cases were analyzed by role theory. Problem solving is a light case settlement activity with mediation. The author provides suggestions based on the findings and discussion, namely the application of mediation in resolving light cases so that the resolution of light cases finds legal certainty and is easily implemented.